THE ROLE OF FERMENTED CEREALS IN THE MODULATION OF THE INTESTINAL MICROBIOTA AND THEIR BENEFITS TO HUMAN HEALTH - Sobczak, Luciene dos Santos; Ribas, Jessyca Caroline Rocha; Florentino, Leandra da Silva; Quadros, Isabela Lima; da Silva, Luciana Alves; da Luz, Renan Gustavo Rodrigues; Pacheco, Okelyton Ayres; de Oliveira, Samara Thais Peixoto (Seven Editora, 2026)
Fermented cereals have emerged as functional foods capable of modulating the gut microbiota and promoting significant health benefits. Fermentation enhances grain digestibility, increases the bioavailability of bioactive compounds, enriches the food matrix with probiotic microorganisms, and intensifies the production of metabolites such as short-chain fatty acids (SCFAs). These metabolites play a key role in intestinal barrier integrity, immune regulation, energy metabolism, and gut–brain axis communication. This review discusses the role of fermented cereals in microbiota modulation, the mechanisms underlying microbial and metabolite activity, and their impact on metabolic, immune, and gastrointestinal health. The evidence evaluated in this review indicates that fermented cereal-based products may contribute to chronic disease prevention, improved digestion, balanced microbiota, and enhanced intestinal function. DOI: https://doi.org/10.56238/sevened2026.008-032